2017
DOI: 10.12738/estp.2017.6.0506
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Middle School Mathematics Textbooks from the Perspective of Fostering Algebraic Thinking through Generalization

Abstract: The efficient use of generalization in textbooks, which are regarded as a supplementary teaching material and constitute a substantial place in the processes of learning and teaching, is important for effective mathematics learning and teaching, as well as for developing mathematical and algebraic thinking. This research seeks to understand how and to what extent middle school mathematics textbooks include both components of generalization in terms of developing algebraic thinking. This study uses the document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Conceptualization of arithmetic as rational numbers in student learning and its transformation into algebra has been recognized as a crucial and difficult issue in student mathematical learning. This study illustrates that students' arithmetic pre-knowledge (Zazkis & Liljedahl, 2002;Kieran & Martínez-Hernández, 2022), and their pre-knowledge of rational numbers (Ni & Zhou, 2005;Gözde & Dilek, 2017) play an important role for in student achievement of algebraic equations and problem solving, and more generally in student learning of the abstract nature of algebra, expressed in symbols (Carraher et al, 2006).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Conceptualization of arithmetic as rational numbers in student learning and its transformation into algebra has been recognized as a crucial and difficult issue in student mathematical learning. This study illustrates that students' arithmetic pre-knowledge (Zazkis & Liljedahl, 2002;Kieran & Martínez-Hernández, 2022), and their pre-knowledge of rational numbers (Ni & Zhou, 2005;Gözde & Dilek, 2017) play an important role for in student achievement of algebraic equations and problem solving, and more generally in student learning of the abstract nature of algebra, expressed in symbols (Carraher et al, 2006).…”
Section: Resultsmentioning
confidence: 70%
“…Learning of rational numbers is a matter of conceptual meaning (Ni & Zhou, 2005;Gözde & Dilek, 2017) from multiplication to fractions and more, a process that successively presupposes adequate prerequisite knowledge of algebra. According to Vygotsky (1986), mathematics is a social construct that implies an ability for abstract thinking.…”
Section: Student Pre-knowledgementioning
confidence: 99%
“…When the research's chosen analytic methodologies were examined, qualitative analysis was shown to be the most popular. Document analysis (Ayber & Tanisli, 2017) and content analysis (Papadopoulos & Patsiala, 2019), on the other hand, have been recognized as analytical tools in qualitative approaches. While inferential statistics are preferred in quantitative techniques, latent class analysis, cluster analysis, and test development analysis are used depending on the study design.…”
Section: Discussionmentioning
confidence: 99%
“…• It is a mathematical modeling process (Ayber & Tanisli, 2017). Kriegler (2007), on the other hand, examined algebraic thinking under two main headings, as seen in Figure 3.…”
Section: Contribution To the Literaturementioning
confidence: 99%
See 1 more Smart Citation